Pengaruh Motivasi Belajar Hafalan Alqur’an Terhadap Ujian Tahfidz - Fauziah, Hapsah; Pramutya, Anggie (MASAGI : Jurnal Pendidikan Agama Islam, 2023)
Motivation is a crucial factor influencing the success of the Tahfidz exam. A student will achieve the desired outcomes in learning if they possess an intrinsic desire to study. Motivation acts as a driving force towards achieving good results, prompting individuals to engage in activities due to an internal drive. However, the reality at SMP IT Al-Khoiriyyah Garut shows that student motivation for learning Tahfidz is significantly lacking. This is evidenced by the finding that 40% of students fail the Tahfidz exam and must undergo intensive memorization quarantine. The Tahfidz exam, faced by ninth-grade students, carries a significant burden. This burden is not only personal but also social, as the exam is witnessed by school authorities and parents alike. Therefore, students must thoroughly master the Qur'anic verses they have memorized to perform smoothly during the exam. The objective of this study is to describe the influence of motivation for memorizing the Qur'an on the Tahfidz exam performance of ninth-grade students at SMP IT Al-Khoiriyyah, Karangpawitan, Garut. This research employs a quantitative correlational approach with simple regression analysis. Data collection methods include observation, document study, and questionnaires distributed to 50 students who served as samples for this study. Data processing was carried out through statistical data analysis. The results indicate that the average score for motivation in memorizing the Qur'an is 3.98, falling within the interval of 3.01-4.00, categorized as "good." Similarly, the average score for the Tahfidz exam is 3.96, also within the interval of 3.01-4.00, categorized as "good." Based on statistical analysis, it is found that motivation for memorizing the Qur'an influences the Tahfidz exam performance by 86.24%. Other factors, which were not explored in this study, account for 13.76%. Keywords: Learning Motivation, Qur'an Memorization, Tahfidz Exam